2015
DOI: 10.1016/j.petlm.2015.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on influencing factors of acid-fracturing effect for carbonate reservoirs

Abstract: Abstract: : : :Acid fracturing treatment is the key technique for stimulation and stable production in carbonate reservoirs. In order to improve the carbonate reservoirs acid fracturing effect, in this paper, with a large number of experiments as the main research methods,study on influencing factors of acid-fracturing effect for carbonate reservoirs from increase the effective distance of living acid, increase acid corrosion eched fracture conductivity, reduce the acid fluid loss, etc. The effective distances… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…This non-uniform coverage of acid in the reservoir could lead to the overall unsuccessful acidizing. Therefore, the Emulsion A, which has viscosity of approximately 50 cp could enhance the zonal coverage, sweep efficiency and acid distribution in heterogeneous reservoirs [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…This non-uniform coverage of acid in the reservoir could lead to the overall unsuccessful acidizing. Therefore, the Emulsion A, which has viscosity of approximately 50 cp could enhance the zonal coverage, sweep efficiency and acid distribution in heterogeneous reservoirs [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Its purpose is dissolving sediments to reinforce rock permeability and the establishment of a clean zone within the reservoir, thus eliminating the restrictions for oil flux into the wellbore zone. Commonly, matrix acidizing is applied in case of tighter carbonate and sandstone formations; it is recommended in industry to utilize acids with mass concentrations, in the range of 10-15%, while acid fracturing is implemented in case of carbonate formations (Bale et al 2010;Li et al 2015;Liang et al 2017;Kolin et al and Kurevija et al 2018) with relatively higher acid mass concentrations, in the range of 20-30%. This method involves acid injection to create channels or so-called wormholes, as the resulting rock fractures, under pressure from the hydrocarbons, might immigrate through.…”
Section: Introductionmentioning
confidence: 99%
“…The particulate materials that are plugging the pore structure will be reducing the rock permeability extensively. In the studies of Li et al (2015), Wilfred and Umeleuma (2015), and Yancheng et al (2017), the effect of rock type, acidizing additives, and other experimental parameters were investigated on crack distributions for reservoir's rocks. Particularly, their experimental procedures widely vary and produce very different results of the treatment processes due to rock impurities.…”
Section: Introductionmentioning
confidence: 99%
“…However, conductivity property of the fractures plays the substantial role in the acid fracturing, regarding the random reactions between rock and acid, and this phenomenon might be difficult to estimate. The factors that would seriously affect this issue are pumping rate of the acid, sufficient length of acidizing propagation, the contact time between acid and rock, closure stress and fluid loss of the acid, etc, and these significant parameters are (Li et al 2015) shown in Fig. 1 specifically.…”
Section: Introductionmentioning
confidence: 99%
“…One of the useful types of acid which is used in these reservoirs is the foamed acid with the immense value of viscosity, low rate of fluid loss, retarding agent property for deep wells and etc. (Chengshou et al 2010;Fufeng et al 2008;Li et al 2015). Mozaffari et al (2015) proposed that other factors which significantly affect the production rate in fractured carbonated reservoirs are the capillary force of liquid in microand nano-sized channels which might be blocked by the asphaltene.…”
Section: Introductionmentioning
confidence: 99%